2018
DOI: 10.1002/ams2.343
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone and cyclosporine A as neuroprotective agents for acute ischemic stroke

Abstract: It is well known that acute ischemic stroke (AIS) and subsequent reperfusion produce lethal levels of reactive oxygen species (ROS) in neuronal cells, which are generated in mitochondria. Mitochondrial ROS production is a self‐amplifying process, termed “ROS‐induced ROS release”. Furthermore, the mitochondrial permeability transition pore (MPTP) is deeply involved in this process, and its opening could cause cell death. Edaravone, a free radical scavenger, is the only neuroprotective agent for AIS used in Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 55 publications
3
55
0
Order By: Relevance
“…The excessive ROS generation can mediate inflammation and immune response by stimulating the expression of cytokines and adhesion molecules, ultimately causing further injury by inflammation, finally leading to ischemia-reperfusion injury (5,6). Edaravone-based neuroprotective therapy is the main strategy for the treatment of ischemic stroke by eliminating the free radicals and suppressing oxidative stress (7)(8)(9). However, its clinical application is limited by the low bioavailability, short half-life, inefficient penetration across the blood-brain barrier (BBB), and the side effects to kidney and liver functions.…”
Section: Introductionmentioning
confidence: 99%
“…The excessive ROS generation can mediate inflammation and immune response by stimulating the expression of cytokines and adhesion molecules, ultimately causing further injury by inflammation, finally leading to ischemia-reperfusion injury (5,6). Edaravone-based neuroprotective therapy is the main strategy for the treatment of ischemic stroke by eliminating the free radicals and suppressing oxidative stress (7)(8)(9). However, its clinical application is limited by the low bioavailability, short half-life, inefficient penetration across the blood-brain barrier (BBB), and the side effects to kidney and liver functions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, combinatorial treatment with Dox and antioxidants has been proposed to eliminate cardiotoxicity and endotheliotoxicity (Soultati et al, 2012;Wang et al, 2015;Akolkar et al, 2017;Abdel-Daim et al, 2017;He et al, 2018). Edaravone (Eda), a free radical scavenger, is the only neuroprotective agent for acute ischemic stroke used in Japan (Matsumoto et al, 2018). It captures and reduces excessive ROS, preventing brain damage.…”
Section: Introductionmentioning
confidence: 99%
“…It captures and reduces excessive ROS, preventing brain damage. Studies have also confirmed that Eda inhibits ROS upstream, closes mitochondrial permeability transition pore (mPTP), prevents mitochondrial dysfunction, and in turn, potentially protects cells (Ikeda and Iwasaki, 2015;Matsumoto et al, 2018). Whether Eda can reduce the damage of VE caused by Dox toxicity is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of cyclosporin and other PTP inhibitors to attenuate NLRP3 inflammasome activation provides a link between PTP and inflammation [ 219 , 220 ]. Several works reported that the inhibition of PTP by genetic or pharmacological approaches confers protection against ischemic damage [ 221 , 222 , 223 ]. Accordingly, it has been observed that ROS generation induced by rotenone injection, are mitigated by the inhibition of PTP or mitochondria ROS scavenger [ 224 ], indicating the important participation of PTP in the activation and sustainment of IS-induced inflammation.…”
Section: Ischemic Stroke and Mitochondrial Induced Neuroinflammatimentioning
confidence: 99%